Simultaneous decrease of plasma obestatin and ghrelin levels after a high-carbohydrate breakfast in healthy women - Sedláčková, D; Dostálová, I; Hainer, V; Beranová, L; Kvasničková, H; Hill, M; Haluzík, M; Nedvídková, J (Physiological research, 2008)
Ghrelin is a gut peptide produced mainly by stomach, well known to induce appetite stimulatory actions. Obestatin, a recently identified peptide derived from preproghrelin, was initially described to antagonize stimulatory effect of ghrelin on food intake. The postprandial response of obestatin and its relationship with ghrelin in humans remains unknown. We therefore investigated the postprandial response of obestatin and total ghrelin, acyl and desacyl ghrelin and neuropeptide Y (NPY) to a high-carbohydrate breakfast (1 604 kJ) in eight healthy women (age: 24.2+/-0.82 years; BMI 21.6+/-0.61 kg/m(2)). Blood samples were collected before the meal, and 30, 60, 90, 120 and 150 min after the breakfast consumption. Postprandial plasma obestatin concentrations significantly decreased compared with preprandial levels as well as total ghrelin concentrations and reached the lowest values 90 and 120 min after the meal consumption, respectively (p<0.05). Plasma acyl and desacyl ghrelin concentrations decreased after the breakfast and reached lowest values in 30 and 60 min, respectively (p<0.05). Plasma NPY concentrations were lower than preprandial levels 90 and 150 min after consuming breakfast (p<0.05). In conclusion, we demonstrated in healthy young women that plasma obestatin concentrations decrease similarly to ghrelin after a high-carbohydrate breakfast.
Keywords: dospělí; peptidové hormony; Eating; Female; ghrelin; Adult; ženské pohlaví; neuropeptid Y; lidé; postprandiální období; Insulin; referenční hodnoty; přijímání potravy; Reference Values; Postprandial Period; Ghrelin; Peptide Hormones; Neuropeptide Y; Dietary Carbohydrates; inzulin; dietní sacharidy; Humans